Analysis Of Under Passing Skills In Learning Volyballs In Man 1 Model, Bengkulu City - Doni Kurniawan; Feby Elra Perdima; Supriyanto Supriyanto (Hanoman Journal: Physical Education and Sport, 2020)
This study aims to: (1) Determine the level of forearm pass skills in volleyball learning in MAN 1 MODEL Bengkulu City. The method used in this research is to use quantitative descriptive analysis method, with the calculation of the study population used as research samples based on calculations in the form of numbers with statistical calculations. The population of this research is 30 students. The data collection technique in this study is a data processing technique that looks at the data analysis of forearm pass skills. The implementation in this study used was to provide an assessment in the form of time used during the test of forearm pass skills in volleyball and observing the implementation of the tests given, after which it was converted to T-score data to see the categories of volleyball forearm pass skills in MAN 1 MODEL Bengkulu City. From the results of the research analysis carried out, namely: 13 people (43.33%) were at a score of ≥ 47, 12 people (40.00%) were at a score of 40-46, 5 people (16.67%) were at a score of 27- 39, 0 people (0%) were in 17-26 and 0 people (%) were at a score 16. Based on the data, the results of the analysis show that the level of basic forearm pass skills in MAN 1 MODEL Bengkulu City is in the good category with an average score of 44.9 forearm pass.